Korelasi Penguasaan Kosakata Dengan Kemampuaan Menulis Wacana Pada Siswa Kelas XI SMA Jaya Negara - Jafar Jafar (Peneliti.net, 2023)
This study aims to describe how the correlation of vocabulary mastery with the ability to write discourse in class XI SMA Jaya Negara. This research is a correlation research. From the research results show that the correlation. index